Archangel's shadows - Singh, Nalini, 1977- (Singh, Nalini, 1977- Guild Hunter series., 2014)
After a bloody battle, the archangel Raphael and his consort, Elena, ask hunter Ashwini and her partner, Cajun vampire Janvier, to stop an insane archangel who is terrorizing the already beaten-down town.